Maze In Numbers: An Educational Game Prototype. - Amir Hamzah, Muhidi (2007)
Video game or more precisely computer games had long been claimed as tools for leisure and entertainment activities only. Using games as a medium to spread knowledge or enhance learning process were still been seen as a skeptical work. Games can be used as educational tools, if the design and implementation were done in a right way. Seeing there are large numbers of commercial games available and people who involve in it, it is quite surprising that the potential of games as educational tools had been overlooked. Based on various past researches, this study attempted to underline some of important facts about the usable of game as an educational tool. In this study a requirement to make a better educational game were sorted out, based on it an educational game prototype were developed and tested against primary school students. The game was based on mathematic subject and using maze and puzzle as its genre.